Misreporting Trade Statistics and Unrecorded Capital Flows : Estimates, Causes and Remedies - Marjit, Sugata et al; Export-Import Bank of India (India Exim Bank) (Mumbai : Export-Import Bank of India (India Exim Bank), 2023)
The main report is divided into seven chapters starting with the introduction. The second chapter is the findings from the field work in four major cities, Chennai, Delhi, Kolkata and Mumbai. The third is the analysis of descriptive statistics on misreporting of trade data. Subsequently the study tries to provide a better measure of balance of trade (BOT) with the help of bilateral mirror data. The fourth chapter deals with similar issues related to mirror data involving capital flows. The fifth chapter is a time series econometric analysis of the relationship between export import mis-matches. The six chapter is a regression analysis of what explains the deviations between the reported and actual data in terms of some critical aggregate explanatory variables. The seventh chapter provides a conclusion and a few key policy insights.
List of Figures -- List of Tables -- Executive Summary -- 1. Introduction -- 2. Field Survey -- 3. Descriptive Statistics -- 4. Mirror Data Analysis of Capital Flow -- 5. Data, Methodology & empirics -- 6. Aggregate Regression Analysis -- 7. Conclusion and Policy Takeaways -- Appendix.
Keywords: Trade Statistics -- India; Misreporting of trade data; Export and import mis-matches; Balance of trade; Capital Flow